2021
DOI: 10.1186/s13148-020-00973-8
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylcytosine profiles of cfDNA are highly predictive of R-CHOP treatment response in diffuse large B cell lymphoma patients

Abstract: Background Although R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) remains the standard chemotherapy regimen for diffuse large B cell lymphoma (DLBCL) patients, not all patients are responsive to the scheme, and there is no effective method to predict treatment response. Methods We utilized 5hmC-Seal to generate genome-wide 5hmC profiles in plasma cell-free DNA (cfDNA) from 86 DLBCL patients before they received R-CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…R-DA-EPOCH (rituximab, doxorubicin, etoposide, prednisone, vincristine, cyclophosphamide) was commonly used for relapsed DLBCL patients [2]. However, existing methods maynot accurately or effectively predict therapeutic efficacy before treatment of DLBCL [9]. Therefore, understanding the potential effect mechanism of the chemotherapeutic agent acting on DLBCL is essential to improve protocols for improving patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…R-DA-EPOCH (rituximab, doxorubicin, etoposide, prednisone, vincristine, cyclophosphamide) was commonly used for relapsed DLBCL patients [2]. However, existing methods maynot accurately or effectively predict therapeutic efficacy before treatment of DLBCL [9]. Therefore, understanding the potential effect mechanism of the chemotherapeutic agent acting on DLBCL is essential to improve protocols for improving patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The results of both studies showed the potential of cfDNA epigenetic markers for the detection of brain gliomas. However, the direct correlation between hydroxymethylome of plasma cfDNA and transcriptome of the underlying tumor revealed in our results implies its unique advantages and future prospects in not only noninvasive molecular diagnostics, but also convenient dynamic monitoring of the tumor progression and therapeutic response 33,34 …”
Section: Discussionmentioning
confidence: 84%
“…Overview of study design. 5hmC library construction for all samples was consistent with previously reported (16,17). The cfDNA samples were endrepaired using the KAPA Hyper Prep Kit (KAPA Biosystems) and then ligated to sequencing adapters.…”
Section: Figurementioning
confidence: 98%